Filogenia molecular de fungos gasteroides das ordens Phallales e Geastrales (Phallomycetidae) - Cabral, Tiara Sousa (2011)
Gasteroids fungi are characterized by the basidiospores maturation inside the basidioma, from which spores liberation occurs in a passive manner. These fungi were once seen as a well definite class of Basidiomycota, but nowadays they are considered an artificial assemblage, because the organisms have independent evolutionary histories forming a polyphyletic group with a vast morphological variety. Despite their diversity, studies with this group in the tropics are incipient, and the phylogenetic relationships of the species from temperate climate remain unknown. Thus, this work aimed to elucidate the phylogenetic relationships of gasteroids fungi from the Geastrales and Phallales orders, with the inclusion of tropical and temperate species, and with these analyses suggest a systematic position of species like Aseroë floriformis and Phallus roseus, as well as to verify if the lignicolous habit can indicate parental relationship in the Geastrum genus. For this, basidiomata were collected at Atlantic rain forest areas, during the rainy season, and the specimen identification followed specific literature for gasteroid fungi. The phylogenetic analyses were performed with Maximum Parsimony and Bayesian Analysis, making use of RPB2 and 28S nuclear genes and atp6 mitochondrial gene. It could be observed on the Phallales dendogram, that Aseroë floriformis did not cluster with A. rubra, and that it has an anterior divergence from all others species of the family Clathraceae used in this analysis, assuming a basal position in the clade. Phallus roseus, which once was recognized as Itajahya, has previous divergence from the group formed by Phallus species. At the Geastrales dendogram, in the group corresponding to Geastrum genus, it could be observed that species with lignicolous habitat clustered in a clade with high support values. So, the results suggest the creation of a new genus to accommodate A. floriformis, and the revalidation of Itajahya, as well as it can be affirmed that the lignicolous habitat on the Geastrum genus in fact indicates parental relationships, and that it has arised only once at the evolutionary history of the genus